3 Buddha Concepts of Comprehension, Awakening, Exaltation: Conceptual Innovation for Encouraged Sustainable Buddhist Agriculture - Suwatthano, Phrakhrupalad Suwat (Journal of Thammawat, 2024)
This article is a link to the knowledge of buddhist principles applied to create a new body of knowledge that will be extended to the idea of ​​ the study of Buddhist agriculture or agriculture on the path of buddhist. Its objective is to present a conceptual innovative with the conceptual set of 3 Buddha Concepts: Comprehension, Awakening, and Exaltation as a principle to promote Buddhist agriculture or agriculture on the path of Buddhist which is like an intellectual tool for creativity, is an abstract work that can be applied to agricultural practices in the buddhist way to be concrete and creative. It is a thought fertilizer with the principle of Comprehension, Awakening, and Exaltation. The study found that 1) Comprehension is the pursuit of knowledge, knowledgeable, and the transfer of knowledge. 2) Awakening is awakening from the old ideas, awakening from the same failure, and awakening from the closures of opportunities for progress. 3) Exaltation is particular the joyful behave of achievement as smiling, cheerful, happy, not anxious. The first and second are the cause of happiness and the last is the result of happiness. The three principles still have an effect to encourage on buddhist agriculture or agriculture on the path of buddhist, can be sustainable both in today and in the future.